2006
DOI: 10.1089/ast.2006.6.546
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Methanogens During Desiccation: Implications for Life on Mars

Abstract: The relatively recent discoveries that liquid water likely existed on the surface of past Mars and that methane currently exists in the martian atmosphere have fueled the possibility of extant or extinct life on Mars. One possible explanation for the existence of the methane would be the presence of methanogens in the subsurface. Methanogens are microorganisms in the domain Archaea that can metabolize molecular hydrogen as an energy source and carbon dioxide as a carbon source and produce methane. One factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 25 publications
(18 reference statements)
1
28
1
Order By: Relevance
“…Mutants of H. salinarum could be isolated that show a considerably higher radiation resistance than D. radiodurans (9). Several species of methanogenic archaea have been shown to be very resistant against desiccation (17,23).…”
Section: Discussionmentioning
confidence: 99%
“…Mutants of H. salinarum could be isolated that show a considerably higher radiation resistance than D. radiodurans (9). Several species of methanogenic archaea have been shown to be very resistant against desiccation (17,23).…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports showed that Methanosarcina spp. and other methanogens could survive desiccation for limited periods of time (6,10,18,21,30). This report quantitatively assesses the survival rates of a methanogenic archaeon after desiccation and subsequent exposure to stress factors that simulate the driest environments on Earth, such as the Antarctic dry valleys and hyperarid core of the Atacama Desert in Chile (14,24).…”
Section: Recovery Of M Barkeri Desiccated Under Different Growth Conmentioning
confidence: 99%
“…Archaea were discussed as one of the most likely life forms on Earth to survive a space flight, and survive or even thrive on Mars (mainly methanogens and halophiles; Kendrick and Kral, 2006;Landis, 2001), but it was unclear, if Archaea even could be found in spacecraft-associated clean rooms.…”
Section: Introductionmentioning
confidence: 99%